2016
DOI: 10.12933/therya-16-372
|View full text |Cite
|
Sign up to set email alerts
|

Density and activity patterns of ocelots in the greater lacandona ecosystem

Abstract: The ocelot is the third largest cat that occurs in Mexico. Despite all the information that has been collected regarding its distribution in the country, little is known about its basic ecology in Mexico. In this study we estimated population density of ocelots and their activity patterns for the Greater Lacandona Ecosystem region. Data were obtained through camera traps. We used 33 camera trap stations that were active during 60 consecutive days. The effective sampling effort was 1,920 trap days. Population d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 44 publications
3
0
0
Order By: Relevance
“…Foster & Harmsen 2012, de la Torre et al 2016, our average MMDM value for ocelots (Table 4) is similar to those obtained in Chiquibul, Belize, using radio-telemetry (Dillon & Kelly 2008). We lacked radio-telemetry data for ocelots in this region, but consider that our ESA is large enough for the estimation of an unbiased MMDM.…”
Section: Discussionsupporting
confidence: 75%
“…Foster & Harmsen 2012, de la Torre et al 2016, our average MMDM value for ocelots (Table 4) is similar to those obtained in Chiquibul, Belize, using radio-telemetry (Dillon & Kelly 2008). We lacked radio-telemetry data for ocelots in this region, but consider that our ESA is large enough for the estimation of an unbiased MMDM.…”
Section: Discussionsupporting
confidence: 75%
“…Our results suggest that in matrix habitat ocelots are adapting their realized niche by shifting to more nocturnal activity in areas of mixed land‐use, likely to facilitate spatial coexistence with humans in these more disturbed areas. This is consistent with other research on ocelots which has shown they decrease diurnal activity in areas with more human disturbance (Cruz et al., 2018; de la Torre et al., 2016) and are more likely to use human trails during the night than during the day (Bolze et al., 2021). This shift to more nocturnal activity has been seen in many species globally (Gaynor et al., 2018) and the consequences of these shifts extend beyond species fitness and population persistence.…”
Section: Discussionsupporting
confidence: 91%
“…Daily activity patterns often reflect the effect of the energy balance (food demand and supply) and the relationship between predators and prey (Schaik and Griffiths 1996), and can be altered by hunting pressure and modifications of the habitat that affect resource availability. The activity pattern of Leopardus pardalis showed a most intense activity at night, plus records in twilight hours, and isolated events during the day; this is consistent with the activity pattern reported by several authors (Ayala et al 2010;Hernández-Pérez et al 2015;Mosquera-Munoz et al 2015;De la Torre et al 2016). This pattern is probably influenced by the nocturnal activity of its potential preys, such as Didelphis marsupialis, Dasypus novenmcinctus, Tamandua mexicana and Sylvilagus floridanus (Martinez 2013).…”
Section: Discussionsupporting
confidence: 91%